Management in a Multicultural Environment - Januszkiewicz, Katarzyna; Wiktorowicz, Justyna (Facets of Managing in Cross-Cultural Diversity, 2021)
Diversity management is indicated as one of the most important challenges faced by contemporary organizations (Roberson 2019; Cletus, Mahmood, Umar and Ibrahim 2018; Januszkiewicz, Bednarska-Wnuk 2017). The ability to take advantage of diversity in the development of the communication process (Okoro, Washington 2012; Evans, Suklun 2017), interpersonal relations (Mamman, Kamoche, Bakuwa 2012), and finally cooperation, is the key factor in building organizational commitment (Luu, Rowley, Vo 2019; Ghasempour, Rahimnia, Ahanchian and Syed 2020) and a competitive advantage based on social capital (Herriot, Pemberton 1995; Han, Han, Brass 2014; Walczak 2011; Aghazadeh 2004). The aim of this chapter is to analyse the methods and tools of multicultural management in organizations including issues such as culture and multiculturalism and their impact on human behaviours in organizations, and intercultural sensitivity (Bennet, Bennet 1993; Sizoo, Plank, Iskat, Serrie 2005; Bhawuk 2009; Paige, Jacobs-Cassuto, Yershova, DeJaeghere 2003). Based on desk research, we also indicate recommendations for managers in multicultural environments. The chapter was created as a part of the Erasmus+ Project: Innovative & Enhanced CPD for Newly Qualified VET Teachers Working with Migrant Students (project No 2018-1-PL01- KA202-050618).